2004
DOI: 10.1046/j.1471-4159.2003.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

α7‐Nicotinic acetylcholine receptors mediate an Aβ1−42‐induced increase in the level of acetylcholinesterase in primary cortical neurones

Abstract: The b-amyloid protein (Ab) is the major protein component of amyloid plaques found in the Alzheimer brain. Although there is a loss of acetylcholinesterase (AChE) from both cholinergic and non-cholinergic neurones in the brain of Alzheimer patients, the level of AChE is increased around amyloid plaques. Previous studies using P19 cells in culture and transgenic mice which overexpress human Ab have suggested that this increase may be due to a direct action of Ab on AChE expression in cells adjacent to amyloid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 64 publications
2
52
1
Order By: Relevance
“…Sberna et al (1997) found that Aβ increases Ca influx and AChE in cultured P19 cells and Hu et al (2003) reported that Aβ increases AChE by reducing enzyme degradation. Fodero, et al (2004) observed that Aβ -induction of AChE in cultured neurons was associated with an agonist effect of Aβ at α7-nicotinic receptors and could be antagonized by inhibitors of α7 nicotinic receptors or of Land N-type calcium channels. An anomalous glycoform of AChE, similar to an isoform seen in AD brain and CSF and which does not bind to Con A has been reported in Tg2576 mice at 4 and 8 months of age before plaque formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sberna et al (1997) found that Aβ increases Ca influx and AChE in cultured P19 cells and Hu et al (2003) reported that Aβ increases AChE by reducing enzyme degradation. Fodero, et al (2004) observed that Aβ -induction of AChE in cultured neurons was associated with an agonist effect of Aβ at α7-nicotinic receptors and could be antagonized by inhibitors of α7 nicotinic receptors or of Land N-type calcium channels. An anomalous glycoform of AChE, similar to an isoform seen in AD brain and CSF and which does not bind to Con A has been reported in Tg2576 mice at 4 and 8 months of age before plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since Aβ is known to increase AChE in cultured embryonal P19 carcinoma cells (Sberna, et al, 1997), in cultured cortical neurons (Fodero, et al, 2004) and in mice administered Aβ intraventricularly (Fu et al, 2006, 16872586), and since increased Aβ is associated with increased AChE in Tg mice overexpressing the CT-100 APP and Aβ (Sberna, et al, 1998) and in the Tg2576 mouse model (Fodero, et al, 2002), we wished to determine whether intraventricular ODN directed to the β-cleavage site would alter cerebral AChE distribution in Tg2576.…”
Section: Introductionmentioning
confidence: 99%
“…However, vice versa, there are also reports that b-amyloid increased AChE in both neuronally differentiated P19 cells and in primary murine cortical cells (23)(24)(25), with b-amyloid (1-42) being more potent than b-amyloid (1-40). The b-amyloid (1-42)-induced enhancement of AChE was found to be mediated through the action b-amyloid on a7 nicotinic acetylcholine receptors (nAChR; 25), indicating that the local increase in AChE around amyloid plaques in Alzheimer's disease may also be a result of a direct action of b-amyloid on a7 nAChR located on terminals around senile plaques (25).…”
Section: Cholinergic Neurotransmission B-amyloid and App Processing mentioning
confidence: 97%
“…It has also been shown that AChEIs intervene with APP cleavage and decrease Aβ-induced toxicity through some mechanisms, including interference of the Aβ production, alteration of the Aβ levels, and formation of the soluble form of APP [101]. AChEIs can also modulate the expression of AChE isoforms; increase the expression of nicotinic receptors, via which nicotine can show its protective effect by suppress Aβ toxicity and Aβ [102].…”
Section: Symptomatic Therapies: Approved Drugs For Treatment In Alzhementioning
confidence: 99%